Oral Lichen Planus or Oral Lichenoid Reaction? A Literature Review - Farzaneh Agha-Hosseini; Mohammad Samami; Fatemeh Tavakol; Elahe Ghasemzadeh Hoseini (Islamic Dental Association of Iran, 2019)
Background and Aim: Oral lichen planus (OLP) is a chronic, inflammatory, T-cell-mediated autoimmune oral mucosal disease. Oral lichenoid lesions develop as a type IV hypersensitivity reaction. Both of these entities are potential precancerous conditions; this adds to their clinical significance. The purpose of this literature review was to detect the similarities and the differences of these lesions to enhance the information of colleagues in managing these groups of patients. Materials and Methods: For this review, we searched Cochrane, Medline, and Embase databases from January 1990 to the end of October 2018. A total of 96 published pa-pers, including review papers, case reports, cohort studies, case-control studies, and meta-analysis studies, were included and analyzed. Results: OLP and oral lichenoid reactions are two distinct diseases. They can be clinically similar but they have different etiologic factors. A histopathological study is necessary to differentiate them. Conclusion: The definitive diagnosis of these conditions is extremely important given their potentially premalignant nature. A timely diagnosis probably results in proper management. Based on the present research, the final differentiation between OLP and oral Lichenoid reactions relies on both clinical and histopathological manifestations according to the modified World Health Organization (WHO) criteria.